(untitled) (Ta’limda raqamli texnologiyalarni tadbiq etishning zamonaviy tendensiyalari va rivojlanish omillari, 2024)
Abstract. This article discusses the main task of androgogy, and mechanism of using standard english language units in pedagogical sphere. Pedagogical technologies and their role in modern educational system. A primary theory of androgogy, the reading endeavor—learning as a genuine value—the tasks of androgogy and its influence on the teaching and learning process.